The Motif of Language Dominance that Used on Coffee Shop Signboards in Padang City - Mauli Denil; I Wayan Simpen; I Nyoman Suparwa; Anak Agung Putu Putra; Ni Made Suryati (RIRAI Publisher, 2024)
This study offers a fresh perspective on Linguistic Landscapes (LL) by employing language mapping to analyze the frequency and distribution of language usage. The population data comprised 60 signboards from coffee shops and tourism spots in Padang city center. Qualitative methods were utilized for data collection, with analysis conducted using GIS (Geographic et al.) and Adobe Photoshop, representing innovative approaches in LL research. The analysis commenced with quantifying language usage, encompassing mono/bi/multilingual forms on coffee shop signboards. Subsequently, language mapping was employed to illustrate language distribution and highlight motif of linguistic dominance that used on coffee shop signboards in specific areas on the map. Findings revealed the presence of 12 languages on coffee shop signage, reflecting the global influence and societal preference for modernization. Despite the prominence of foreign languages, Indonesian emerged as the most frequently used, indicating relatively successful implementation of Presidential Regulation No.63 of 2019, although inconsistencies persist